2015
DOI: 10.1007/s11682-015-9455-8
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal lobe structural integrity and trail making test, part B: converging findings from surface-based cortical thickness and voxel-based lesion symptom analyses

Abstract: Surface-based cortical thickness (CT) analyses are increasingly being used to investigate variations in brain morphology across the spectrum of brain health, from neurotypical to neuropathological. An outstanding question is whether individual differences in cortical morphology, such as regionally increased or decreased CT, are associated with domain-specific performance deficits in healthy adults. Since CT studies are correlational, they cannot establish causality between brain morphology and cognitive perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 74 publications
(105 reference statements)
0
22
0
Order By: Relevance
“…This result was maintained even after control for total and sedating drug daily doses, age at epilepsy onset, and seizure control. Trail Making Test B demands a complex processing that includes visuomotor coordination, sequencing, cognitive flexibility, and processing speed, and is sensitive to frontal lobe damage [50]. This particular JME group, in which more than one epileptic network seems to be involved in seizure generation as testified through specific reflex traits, also had the higher impairment in Trail Making Test B.…”
Section: Neuropsychological Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…This result was maintained even after control for total and sedating drug daily doses, age at epilepsy onset, and seizure control. Trail Making Test B demands a complex processing that includes visuomotor coordination, sequencing, cognitive flexibility, and processing speed, and is sensitive to frontal lobe damage [50]. This particular JME group, in which more than one epileptic network seems to be involved in seizure generation as testified through specific reflex traits, also had the higher impairment in Trail Making Test B.…”
Section: Neuropsychological Resultsmentioning
confidence: 87%
“…Trail Making Test B has been frequently used in neuropsychological research due to its reliability and sensitivity to executive dysfunction for patients with neurological disorders [50]. In a fMRI study, patients with frontal lesions showed the most consistent performance decrements in this neuropsychological test and had a more localized activation in left dorsomedial prefrontal cortex [50].…”
Section: Neuropsychological Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of structural neuroimaging studies showed that the performance on these tests is related to the volume of the prefrontal cortex, mainly the lateral and medial parts of it (Yuan and Raz 2014 ). Recent studies have also shown an association between the dorsomedial prefrontal cortex and TMT B performance (Miskin et al 2016 ) and between DLPFC and WCST (Boschin et al 2016 ). This may indicate that a DLPFC abnormality in bipolar patients plays a role for both mentalization deficits and cognitive disorders.…”
Section: Discussionmentioning
confidence: 98%
“…Another large-sample study of individuals with penetrating head injuries (N = 182) reported an association between regionally non-specific lesions within the left prefrontal cortex, anterior cingulate, insula, parietal and temporal areas and lower executive functioning, as evaluated by the Delis-Kaplan Executive Function System (D-KEFS) tests that included the TMT ( Barbey et al., 2012 ). Furthermore, damage to the left dorsomedial prefrontal cortex was associated with slower set-switching in a study of 27 frontal chronic brain-injured patients with heterogeneous aetiologies ( Miskin et al., 2016 ). Finally, lesions within the right dorsolateral prefrontal cortex predicted higher incidence of set-switching errors in a sample of 30 acute, right-hemispheric and predominantly frontal stroke patients ( Kopp et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%